A phase 2 trial of the efficacy and safety of elotuzumab in combination with pomalidomide, carfilzomib and dexamethasone for high-risk relapsed/refractory multiple myeloma. Issue 4 (21st March 2022) - Yashar, David; Spektor, Tanya M.; Martinez, Daisy; Ghermezi, Matthew; Swift, Regina A.; Eades, Benjamin; Schwartz, Gary; Eshaghian, Shahrooz; Lim, Stephen; Vescio, Robert; Berenson, James R.
Abstract: High-risk multiple myeloma (MM) continues to have a poor prognosis and remains a therapeutic challenge. This phase 2 study evaluated the efficacy and safety of elotuzumab in combination with pomalidomide, carfilzomib, and low-dose dexamethasone for patients with high-risk relapsed/refractory (RR)MM (NCT03104270). Of 13 enrolled patients, 11 were evaluable for efficacy. Overall response rate and clinical benefit rate were 45.4% and 54.5%, respectively. Deep responses were observed including two complete responses. The novel quadruplet combination was overall well-tolerated, with clinically manageable adverse events. Common adverse events of ≥ grade 3 included lymphopenia (15%), anemia (15%), sepsis (15%), pneumonia (15%), and hypophosphatemia (15%). The novel combination showed promising efficacy and was well tolerated in this heavily pretreated MM population. Even though the study was terminated early prior to completion of enrollment, the results indicate that this may be a promising therapeutic approach for high-risk RRMM patients, which warrants further study.